The Role of the Intelligence Unit in Carrying Out Early Detection of Public Security Disorders Caused by Illegal Mining in the Jurisdiction of the Magelang City Police Department in Order to Maintain Public Security and Order - Depari, Hezkiel (Advances in Police Science Research Journal, 2024)
This study aims to determine the role of the Intelkam unit in detecting early disturbances in public safety and order caused by Ilegal mining in the jurisdiction of Polresta Magelang and to identify supporting and inhibiting faktors in carrying out this task. The method used in this research is descriptive with a qualitative approach. Data collection techniques used were observation, interviews, and documentation. Research informants consisted of Intelkam members, relevant officials, and the community affected by Ilegal mining. The results showed that the Intelkam unit plays a crucial role in detecting early disturbances in public safety and order caused by Ilegal mining in the jurisdiction of Polresta Magelang. However, there are several inhibiting faktors such as a shortage of Intelkam members, inadequate facilities and infrastructure, and a lack of support from superiors. Based on the results, it is recommended that Polresta Magelang increase the number of Intelkam members, provide adequate facilities and infrastructure, and improve support from superiors in carrying out the task of detecting early disturbances in public safety and order caused by Ilegal mining. It is hoped that this research will provide benefits to Polresta Magelang in improving public safety and order in its area.